Conceptual design for Web GIS in pest and disease control system for paddy crop - Zainal Abidin, Faten Nur’ Syahira (2018)
Rice is a staple food in Malaysia, and the self-sufficient level (SSL) of rice is 71.5%. Malaysian government has decided to increase SSL level-up to 100% by 2020. The rice production can be increased by good management and best practices in the rice cultivation. Farmers need to be train to apply the fertilizer, herbicides and pesticides in an efficient way to improve the rice productivity. The information of pest and disease is very important for farmers to avoid any outbreak during planting season. Internet is widely used in the world and it gives a big opportunity for farmers to access the information for pest and disease in rice. Thus, the online integrated systems of pest and disease will help farmers to find a solution to manage the rice field. The online system will provide pest and disease information and helps farmers to do a decision based on the guidelines. The objectives of the research was to identify the current web-based of pest and disease in rice and design a conceptual of the system in user-friendly interface of pest and disease information using web-based application. The methodology of this research involved with two phases. The first phase was investigating the current web-based pest and disease information in rice, and the second phase was to design the conceptual of pest and disease information based on the literature review. Result from this research were a comprehensive conceptual design for online pest and disease framework for rice. The online pest and disease can be developed based on the outcome of this research in the future. This research is a stepping stone to implement the internet of things (IoT) in agriculture. The online system will help farmers to get the pest and disease information and how to control pest and disease in the rice field. Finally, the productivity will b increase by a good management in the rice field. The same concept can be used for other crop like oil palm, rubber, pineapple and corn.